Karakteristik Status Gizi Pasien Anak Leukemia Limfoblastik Akut (LLA) Sebelum dan Sesudah Kemoterapi di RSUD Al-Ihsan Bandung - Putri Aulya Mustafa Yasin; Agung Firmansyah Sumantri; Abdul Hadi Hassan (Bandung Conference Series: Medical Science, 2024)
Abstract. Leukemia is a malignant disease of abnormal white blood cells in the bone marrow. One of the treatments for leukemia patients is chemotherapy which can affect nutritional status. Nutritional status is a person's health status which is related to energy intake in the form of food in a person's country. This study aims to determine the characteristics of nutritional status in pediatric acute lymphoblastic leukemia (ALL) patients before and after chemotherapy. The sample selection technique used a total sampling technique from the entire population of ALL pediatric patients at Al-Ihsan Hospital, Bandung Regency. This research uses an analytical observational method with a cross-sectional approach. The data used is secondary data taken from pediatric patients with LLA in the form of medical record data at Al-Ihsan Regional Hospital, Bandung. The research results showed that the majority of patients before chemotherapy had normal nutritional status, 34 subjects (52.3%), and the majority of patients after chemotherapy had normal nutritional status, 40 subjects (61.5%). Child patients with ALL before chemotherapy had normal nutritional status as many as 34 people (52.3%), overweight nutritional status as many as 3 people (4.6%), and with underweight nutritional status as many as 28 people (43.1%). with ALL after chemotherapy had normal nutritional status as many as 40 people (61.5%), overweight nutritional status as many as 3 people (4.6%), and with underweight nutritional status as many as 22 people (33.8%) These results were caused by errors one factor is chemotherapy drugs which are corticosteroids. The use of corticosteroid drugs can increase appetite which can be a factor in improving the patient's nutritional status during chemotherapy treatment. Abstrak. Leukemia merupakan penyakit keganasan pada sel darah putih abnormal di sumsum tulang, salah satu pengobatan pada pasien leukemia salah satunya adalah kemoterapi yang dapat berpengaruh terhadap status gizi. Status gizi merupakan status kesehatan seseorang yang berkaitan dengan asupan energi berupa makanan di negara seseorang. Penelitian ini bertujuan untuk mengetahui karakteristik status gizi pada pasien anak leukemia limfoblastik akut (LLA) sebelum dan sesudah melakukan kemoterapi. Teknik pemilihan sampel menggunakan teknik total sampling dari seluruh populasi pada pasien anak LLA di Rumah Sakit Al-Ihsan Kabupaten Bandung. Penelitian ini menggunakan metode observasional analitik dengan pendekatan potong lintang. Data yang digunakan merupakan data sekunder yang diambil pada pasien anak LLA berupa data rekam medik di RSUD Al-Ihsan Bandung. Hasil penelitian menunjukkan data mayoritas pasien sebelum kemoterapi memiliki status gizi normal 34 subjek (52.3%), dan mayoritas pasien setelah dilakukan kemoterapi memiliki status gizi normal 40 subjek (61.5%). Pasien anak dengan LLA sebelum kemoterapi memiliki status gizi normal sebanyak 34 orang (52,3%), status gizi overweightsebanyak 3 orang (4,6%), serta dengan status gizi underweight sebanyak 28 orang (43,1%).Pasien anak dengan LLA sesudah kemoterapi memiliki status gizi normal sebanyak 40 orang (61,5%), status gizi overweight sebanyak 3 orang (4,6%), serta dengan status gizi underweight sebanyak 22 orang (33,8%) Hasil ini disebabkan karena salah satu faktor berupa obat kemoterapi yang merupakan golongan kortikosteroid. Penggunaan obat kortikosteroid dapat meningkatkan nafsu makan yang dapat menjadi faktor meningkatnya status gizi pasien saat pengobatan kemoterapi.